A highly resolved record of relative sea level in the western Mediterranean Sea during the last interglacial period. Issue 11 (November 2018) - Polyak, Victor; Onac, Bogdan; Fornós, Joan; Hay, Carling; Asmerom, Yemane; Dorale, Jeffrey; Ginés, Joaquín; Tuccimei, Paola; Ginés, Angel
Abstract The magnitude and trajectory of sea-level change during marine isotope stage (MIS) 5e of the last interglacial period is uncertain. In general, sea level may have been 6–9 m above present sea level, with one or more oscillations of up to several metres superimposed. Here we present a well-dated relative sea-level record from the island of Mallorca in the western Mediterranean Sea for MIS-5e, based on the occurrence of phreatic overgrowths on speleothems forming near sea level. We find that relative sea-level in this region was within a range of 2.15 ± 0.75 m above present levels between 126, 600 ± 400 and 116, 000 ± 800 years ago, although centennial-scale excursions cannot be excluded due to some gaps in the speleothem record. We corrected our relative sea-level record for glacio-isostatic adjustment using nine different glacial isostatic models. Together, these models suggest that ice-equivalent sea-level in Mallorca peaked at the start of MIS-5e then gradually decreased and stabilized by 122, 000 years ago, until the highstand termination 116, 000 years ago. Our sea-level record does not support the hypothesis of rapid sea-level fluctuations within MIS-5e. Instead, we suggest that melting of the polar ice sheets occurred early in the interglacial period, followed by gradual ice-sheet growth. A sea-level record from Mallorca shows no evidence of large, millennial-scale oscillations during the last interglacial.